(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The adoption of green economy principles in traditional industries offers opportunities for sustainable development while preserving cultural identity. Batik Village in Sidoarjo Regency, East Java, represents a local effort to transition toward environmentally responsible production practices. This study aims to evaluate how green economy concepts are implemented in batik production and to identify their perceived effects on sustainability, artisans’ welfare, and community participation. Employing a qualitative descriptive design, data were collected through in-depth interviews with ten batik artisans, focus group discussions with local leaders, and document reviews of village programs. Data were analyzed thematically to explore the extent of green practices and their socio-economic implications. The results show that while the community demonstrates awareness of eco-friendly production—such as reducing chemical dyes and reusing water—implementation remains inconsistent due to limited resources, lack of training, and weak institutional support. Several artisans have initiated small-scale innovations, such as natural dye experimentation and waste segregation, yet these efforts have not been systematically evaluated for effectiveness. Stakeholders emphasized the need for technical assistance, sustainable funding, and clearer indicators to measure environmental and economic outcomes. In conclusion, the study highlights that the integration of green economy principles in Batik Village is at an early stage, characterized by community willingness but constrained by capacity and policy gaps. Strengthening evaluation frameworks and collaborative governance is essential to transform these initiatives into measurable sustainable progress.